2020
DOI: 10.9734/ijtdh/2020/v41i1130332
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity of Some Plants Extracts and Their Partitioned Fractions against Culex quinquefasciatus

Abstract: Aim: The methanol extracts of fifteen plants and their partitioned fractions were screened for larvicidal activity against the fourth instar of larvae Culex quinquefasciatus, the vector of lymphatic filariasis with a view to identifying the active ones. Methodology: The plant parts were collected, separately dried and milled. Each powdered material was extracted in methanol at room temperature for 3 days, with agitation. The extract was filtered and concentrated in vacuo. Each extract was tested against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…aegypti [31] . Similarly, research conducted on the fruit extract of Thevetia neriifolia and the leaf extracts of Calotropis procera and Solanum macrocarpon had moderate (about 56%) larvicidal activity after 48 hours [32] . This present study revealed that methanolic extract of the seed part of P. dactylifera showed greater larvicidal activity of 52% and 20% at concentrations of 1000 and 250 ppm, respectively, against the IV instar larvae of Ae.…”
Section: Discussionmentioning
confidence: 92%
“…aegypti [31] . Similarly, research conducted on the fruit extract of Thevetia neriifolia and the leaf extracts of Calotropis procera and Solanum macrocarpon had moderate (about 56%) larvicidal activity after 48 hours [32] . This present study revealed that methanolic extract of the seed part of P. dactylifera showed greater larvicidal activity of 52% and 20% at concentrations of 1000 and 250 ppm, respectively, against the IV instar larvae of Ae.…”
Section: Discussionmentioning
confidence: 92%
“…The Anacardiaceae family has approximately 81 genera subdivided into 800 species, present mainly in tropical and subtropical regions (Pell, 2011). It is a family with plants known for food consumption, but many of these species have insecticidal potential against mosquitoes vectors of diseases such as Anacardium occidentale L. (Vani et al, 2018;Kala et al, 2019) and Spondias mombin L. (Famuyiwa et al, 2020;Ajaegbu et al, 2016), known as cashew and yellow mombin, respectively. In addition to these, the genus Schinus has species widely distributed throughout the Brazilian territory, among them, Schinus molle L., which is investigated in the control of urban disease vectors such as Culex pipiens (Diptera: Culicidae) for example (Zahran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%